Optimal intestinal graft selection for reconstruction of extended ureteral stricture: an animal model study - S. V. Kotov; R. I. Guspanov; A. G. Yusufov; O. V. Gaina; A. L. Aprosimov; I. V. Lapin; M. M. Zobnin; N. O. Larionova; N. V. Trykina; T. Yu. Luskatova; O. V. Bogdanova (Вестник урологии)
Introduction. The prevalence of patients with extended ureteral strictures has been steadily increasing over the past decades. When it is not possible to perform reconstruction with the tissues of the urinary system, the best solution is intestinal replacement plasty. However, despite the great world experience, the search for the optimal method of intestinal reconstruction does not stop, which determines the relevance of conducting an experimental prospective study.Objective. To evaluate morphological changes in renal parenchyma after ureteral replacement reconstruction by segments of small and large intestine.Materials & methods. Fifteen white giant rabbits (6-months-old, weighing 5 kg) were divided into three groups. Group A (n = 5) underwent small intestine [ilealplasty] replacement plasty. Group B (n = 5) double-flap ileoplasty using the Yang-Monti technique. Group C (n = 5) – large intestine [coloplasy] ureteral reconstruction. Before the operation and before withdrawal from the experiment, the level of creatinine and electrolytes was assessed, kidney ultrasound was performed on days 2, 5, 10. Excretory urography was performed to assess the patency of the anastomoses. Animals were withdrawn from the experiment from day 10 to 30. The material used for morphological study included kidneys from the operated and intact sides, proximal and distal anastomoses.Results. No increase in creatinine level, metabolic disorders were detected in animals. According to ultrasound data, hydronephrosis developed in all animals on day 2 and remained unchanged during the entire follow-up. Group A: no complications were detected. Histologically, the renal parenchyma showed moderate signs of chronic inflammation, single foci of lymphoid infiltration, but there were no irreversible processes in the form of necrosis and sclerosis. Group B: complications — stricture in the anastomosis area of the detubularised fragments and necrosis of the small intestine due to compression of the mesentery by the graft vascular stem. Histologically there were marked dilatation of the tubules at all levels, enlargement of the Bowman-Shumlansky capsule, as well as signs of moderate inflammatory process, there were hydropic and hyaline-droplet dystrophy, tubular necrosis foci. Group C: complications — accumulation of a significant amount of grit, mucus, and fibrin in the colocystoanastomosis area. Histologically, the renal parenchyma showed a marked inflammatory process, in particular, purulent inflammation with demarcation zones, infiltration with polymorphonuclear leukocytes and bacterial cells, foci of necrosis and sclerosis of both stroma and tubules, dilatation of tubules and Bowman-Schumlansky capsules.Conclusion. The use of an unchanged ileal-graft reconstruction of an extended ureteral defect showed acceptable histological results in an animal model, which confirms the feasibility of its use in clinical practice. The absence of foci of necrosis and fibrosis in the renal parenchyma indicates the preserved functional potential, which suggests the stabilization of renal function in the long term.